México into the globalization: Nuevo León, the safe border for international trade program (México en la globalización: Nuevo León, programa de frontera segura para el comercio exterior) - Barragán Codina, José Nicolás (Facultad de Contaduría Pública y Administración U.A.N.L., 2006)
Abstract. The presentation of this research paper in the 10th. annual Conference of the Western Hemispheric Development in the University of Texas A&M in Laredo Texas, (April 23-25, 2005) brought a great opportunity to reflect the efforts of a region in the north of Mexico for the world’s peace and security inside the International trade with the gowth factors important for any and all nations. In this investigation the combined efforts of USA and Mexico are shown to protect the International Trade against the acts of terrorism and smuggling of illegal drugs which constantly try to infiltrate their illicit activities, delivering a great damage to companies that carry out activities of international trade. Relevant conclusions are presented at the end of the paper. Resumen. La oportunidad de presentar esta ponencia dentro de la 10 anual Conferencia del Wester Hemispherif Develomptment, en la Universidad de Texas A&M en Laredo Texas, (Abril 23- 25, 2005) fue una gran oportunidad para mostrar los esfuerzos de una región del norte de México por la paz y seguridad dentro del Comercio Internacional, que es en si uno de los factores de desarrollo mas importante para cualquier nación. En esta investigación se muestran los esfuerzos conjuntos d EEUU y México para proteger el Comercio Internacional de los actos de terrorismo y contrabando de drogas ilegales, que desgraciadamente utilizan este medio, para infiltrar sus actividades ilícitas, y por ende, es una gran perjuicio para compañías que honestamente realizan actividades de comercio internacional. Así mismo, se presentan las conclusiones sobre estas discusiones al final de artículo.